Research on the stability of loess landslides under seismic action based on simplified bishop method - Hu, Guirang; Li, Bin; Yan, Xiaobing; Ren, Ruiguo; Zeng, Jinyan (Frontiers in Earth Science, 2024)
Assessing the stability of loess landslides under seismic action scientifically and reasonably is crucial for reducing earthquake disasters and ensuring the safety of people’s lives and property. To study this issue, we chose the southern part of Fushan County, Shanxi Province as the research area, where loess slopes develop and earthquake impacts are strong. Based on the high-precision DEM images of the study area obtained from the unmanned aerial vehicle photogrammetry, we selected 32 representative profiles by sampling according to our principles, and used the simplified Bishop method popular in engineering for modeling and calculation to evaluate the stability of the entire slopes in the area. The calculation results were then statistically analyzed, and the stability and impact range of the slopes were evaluated by means of the graphical form. The results show that in the study area the value of slope safety coefficient (Fs) is mostly within a range of 0.7–1.35 and the value of the avoidance distance is mostly within a range of 5–20 m under a seismic force of 0.20 g, and the slope safety coefficient is mainly determined by the slope angle, and the avoidance distance is mainly determined by the slope height, which is in line with the conclusions of previous research conclusions. In the paper we make a useful attempt for quantitative evaluation of regional seismic loess landslides, and the fact proves that the approach is feasible and efficient, and it can provide quantitative data for major construction projects to avoid landslide disasters.